Analysis of SARS-CoV-2 Emergent variants following AZD7442 (tixagevimab/cilgavimab) for early outpatient treatment of COVID-19 (TACKLE trial) - Kijak, GH; Ahani, B; Arbetter, D; Chuecos, F; Gopalakrishnan, V; Beloor, J; Brady, T; Nguyen, A; Roe, TL; Schuko, N; Zhang, T; Hobbs, FDR; et al. (Springer Nature, 2023)
Introduction: AZD7442 (tixagevimab/cilgavimab) comprises neutralising monoclonal antibodies (mAbs) that bind to distinct non-overlapping epitopes on the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein. Viral evolution during mAb therapy can select for variants with reduced neutralisation susceptibility. We examined treatment-emergent SARS-CoV-2 variants during TACKLE (NCT04723394), a phase 3 study of AZD7442 for early outpatient treatment of coronavirus disease 2019 (COVID-19). Methods: Non-hospitalised adults with mild-to-moderate COVID-19 were randomised and dosed ≤ 7 days from symptom onset with AZD7442 (n = 452) or placebo (n = 451). Next-generation sequencing of the spike gene was performed on SARS-CoV-2 reverse-transcription polymerase chain reaction-positive nasopharyngeal swabs at baseline and study days 3, 6, and 15 post dosing. SARS-CoV-2 lineages were assigned using spike nucleotide sequences. Amino acid substitutions were analysed at allele fractions (AF; % of sequence reads represented by substitution) ≥ 25% and 3% to 25%. In vitro susceptibility to tixagevimab, cilgavimab, and AZD7442 was evaluated for all identified treatment-emergent variants using a pseudotyped microneutralisation assay. Results: Longitudinal spike sequences were available for 461 participants (AZD7442, n = 235; placebo, n = 226) and showed that treatment-emergent variants at any time were rare, with 5 (2.1%) AZD7442 participants presenting ≥ 1 substitution in tixagevimab/cilgavimab binding sites at AF ≥ 25%. At AF 3% to 25%, treatment-emergent variants were observed in 15 (6.4%) AZD7442 and 12 (5.3%) placebo participants. All treatment-emergent variants showed in vitro susceptibility to AZD7442. Conclusion: These data indicate that AZD7442 creates a high genetic barrier for resistance and is a feasible option for COVID-19 treatment.